PERAN PARAMETER HEMOREOLOGI DAN HEMOSTASIS SEBAGAI FAKTOR PROGNOSIS STROKE ISKEMIK AKUT DENGAN COVID-19 - Al Rasyid (PERDOSNI, 2021)
Heretofore Coronavirus Disease-2019 (COVID-19) is still a serious global health threat. COVID-19 manifests not only in the respiratory system but also in the nervous system, one of which is acute ischemic stroke. There may be a reciprocal association between COVID-19 and acute ischemic stroke. Infection that occurs in COVID-19 offers detrimental effects on blood viscosity and the coagulation system. Disturbance of blood viscosity and coagulation system would cause deceleration of blood ????ow and thromboembolic, hence predisposing ischemic stroke. Disturbance of both parameters is also associated with worsening outcomes in ischemic stroke and COVID-19, as evaluated by the modified Rankin scale (mRS), Barthel index (BI) and mortality rate. Keywords: Acute ischemic stroke, blood viscosity, coagulopathy, COVID-19